Catalytic enantioselective arylative cyclizations of alkynyl 1, 3-diketones by 1, 4-rhodium(i) migration. Issue 10 (11th February 2020) - Groves, Alistair; Sun, Jinwei; Parke, Hal R. I.; Callingham, Michael; Argent, Stephen P.; Taylor, Laurence J.; Lam, Hon Wai
Abstract : The enantioselective synthesis of densely functionalized polycarbocycles by the rhodium(i )-catalyzed reaction of arylboronic acids with alkynyl 1, 3-diketones is described. The key step in these reactions is an alkenyl-to-aryl 1, 4-Rh(i ) migration.. Abstract : The enantioselective synthesis of densely functionalized polycarbocycles by the rhodium(i )-catalyzed reaction of arylboronic acids with 1, 3-diketones is described. The key step in these desymmetrizing domino addition–cyclization reactions is an alkenyl-to-aryl 1, 4-Rh(i ) migration, which enables arylboronic acids to function effectively as 1, 2-dimetalloarene surrogates.